Neogene-Quaternary tectonic regime and macroseismic observations in the Tyrnavos-Elassona broader epicentral area of the March 2021, intense earthquake sequence - Galanakis, Dimitrios; Sboras, Sotiris; Konstantopoulou, Garyfalia; Xenakis, Markos (Bulletin of the Geological Society of Greece, 2021)
On March 3, 2021, a strong (Mw6.3) earthquake occurred near the towns of Tyrnavos and Elassona. One day later (March 4), a second strong (Mw6.0) earthquake occurred just a few kilometres toward the WNW. The aftershock spatial distribution and the focal mechanisms revealed NW-SE-striking normal faulting. The focal mechanisms also revealed a NE-SW oriented extensional stress field, different from the orientation we knew so far (ca. N-S). The magnitude and location of the two strongest shocks, and the spatiotemporal evolution of the sequence, strongly suggest that two adjacent fault segments were ruptured respectively. The sequence was followed by several coseismic ground deformational phenomena, such as landslides/rockfalls, liquefaction and ruptures. The landslides and rockfalls were mostly associated with the ground shaking. The ruptures were observed west of the Titarissios River, near to the Quaternary faults found by bore-hole lignite investigation. In the same direction, a fault scarp separating the alpidic basement from the alluvial deposits of the Titarissios valley implies the occurrence of a well-developed fault system. Some of the ground ruptures were accompanied by extensive liquefaction phenomena. Others cross-cut reinforced concrete irrigation channels without changing their direction. We suggest that this fault system was partially reactivated, as a secondary surface rupture, during the sequence as a steeper splay of a deeper low-to-moderate angle normal fault.